A bundle-free implicit programming approach for a class of elliptic MPECs in function space - Hintermüller, M.; Surowiec, T. (Mathematical programming, 2016)
Using a standard first-order optimality condition for nonsmooth optimization problems, a general framework for a descent method is developed. This setting is applied to a class of mathematical programs with equilibrium constraints in function space from which a new algorithm is derived. Global convergence of the algorithm is demonstrated in function space and the results are then illustrated by numerical experiments.